Phase 1 study of epacadostat in combination with atezolizumab for patients with previously treated advanced nonsmall cell lung cancer. Issue 7 (20th March 2020) - Hellmann, Matthew D.; Gettinger, Scott; Chow, Laura Q. M.; Gordon, Michael; Awad, Mark M.; Cha, Edward; Gong, Xiaohua; Zhou, Gongfu; Walker, Chris; Leopold, Lance; Heist, Rebecca S.
Abstract : Epacadostat is a potent and highly selective inhibitor of indoleamine 2, 3‐dioxygenase 1 (IDO1). Here we report results from the open‐label, dose‐escalation, Phase 1b ECHO‐110 study evaluating epacadostat plus atezolizumab in patients with previously treated Stage IIIB/IV nonsmall cell lung cancer (NSCLC). Eligible patients had received ≥1 prior line of platinum‐based chemotherapy (≥2 cycles) and no prior checkpoint/IDO inhibitors treatment. Oral epacadostat (25, 50, 75, 100, 200 or 300 mg) was administered twice daily (BID) with intravenous atezolizumab 1, 200 mg every 3 weeks (Q3W). Primary endpoints were safety, tolerability and dose‐limiting toxicities (DLTs). Twenty‐nine patients received ≥1 dose of treatment. The maximum tolerated dose of epacadostat was not reached. Two patients had DLTs: one patient with Grade 3 dehydration and hypotension (epacadostat 200 mg BID); one patient with Grade 3 hyponatremia and Grade 4 autoimmune encephalitis (epacadostat 300 mg BID). Twenty‐three patients (79%) had treatment‐related adverse events (AEs); seven patients (24%) experienced Grade 3/4 events; five patients (17%) discontinued treatment due to treatment‐related AEs. No fatal treatment‐related AEs occurred. One patient achieved a partial response (objective response rate, 3%), which was maintained for 8.3 months; eight patients had stable disease. Baseline tumoral programmed cell death ligand 1 (PD‐L1) and IDO expression were low among patients with evaluable samples (1 of 23 expressed PD‐L1; 5 of 17 expressed IDO). Epacadostat pharmacokinetics was comparable to historical controls. Epacadostat, at doses up to 300 mg BID, combined with atezolizumab 1, 200 mg Q3W was well tolerated in patients with previously treated NSCLC, although clinical activity was limited. Abstract : What's new? There has been considerable interest in investigating combination treatment strategies that target separate but complementary immune‐evasion pathways, in patients with advanced non‐small‐cell lung cancer (NSCLC). The goal is to enhance the efficacy of immune checkpoint inhibitors. In this study, the authors found that combining the IDO1 enzyme inhibitor epacadostat with the PD‐L1 checkpoint inhibitor atezolizumab was generally well tolerated. However, clinical activity was limited. These results provide important insights into the challenges associated with developing combination immunotherapies in NSCLC.